Gendola Leaf Ethyl Acetate Fraction (Basella rubra Linn) Reduces Spermatozoa Motility and Viability in Vitro - Lusia Hayati; Joko Marwoto; Septi Purnamasari; Yuni Fitriayanti (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2021)
A B S T R A C TBackground. The use of plants as anti-fertility in men has been done to reduce sideeffects. The Gendola plant is one of the Basellaceae family plants, which is a naturalmedicinal plant in Indonesia. Gendola leaves contain phenol compounds, flavonoids,tannins, steroids and triterpenoids which can have cytotoxic activity. This studyaims to determine the in vitro anti sperm activity of the ethyl acetate fraction ofGendola leaves on male spermatozoa. Methods. This study is an experimentallaboratory in vitro study using male sperm preparations. The sample used was 20men for each group, both the group was given the gondola leaf fraction and thecontrol group. The treatment group was given ethyl acetate fraction of Gendola leaves(Basella rubra Linn.) With a concentration of 0.05% for 5, 10 and 15 minutes, theviability and motility of sperm were calculated. Data analysis was performed usingthe Mann Whitney test (p <0.05) using SPSS release for Windows software. Results.The results showed that the ethyl acetate fraction affected the motility and viabilityof spermatozoa. When compared with the control group, the motility treatment groupobtained was classified as non-progressive. In the treatment group, the viability ofspermatozoa was significantly different at minute 5, minute 10 and minuted 15 (p<0.05). Conclusion. Ethyl acetate fraction has potential as an anti sperm inreducing sperm motility and viability.